2003
DOI: 10.1007/s00431-003-1247-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fat mass, fat-free mass and aerobic fitness in severely obese children and adolescents following a residential treatment programme

Abstract: A moderate dietary restriction in combination with physical activity and psychological support in severely obese children and adolescents is effective in decreasing body fat and improving physical performance. Further research is needed to evaluate the longer-term effects of such a programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 49 publications
8
49
2
2
Order By: Relevance
“…It has been suggested that moderate aerobic training at least twice a week for at least six weeks may improve the metabolic profile 6,16,18 and cardiovascular fitness 1,7,12,13,20,38 . Our proposal consisted of a workload of 120 min/week of moderate physical activity (40 to 75% of VO2peak), divided into three weekly sessions, combined with nutritional guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that moderate aerobic training at least twice a week for at least six weeks may improve the metabolic profile 6,16,18 and cardiovascular fitness 1,7,12,13,20,38 . Our proposal consisted of a workload of 120 min/week of moderate physical activity (40 to 75% of VO2peak), divided into three weekly sessions, combined with nutritional guidance.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true because such investigations require a multidisciplinary team and longterm study to detect the changes induced in this population [20][21] . Thus, the aim of the present study was to evaluate the effect of physical training and nutritional guidance on body composition, physical fitness, lipid profile and insulin resistance among obese adolescents with and without metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…For example, since the early 1980s, there have been only 13 published randomised controlled trials (RCTs) of obesity management among adolescents. [28][29][30][31][32][33][34][35][36][37][38][39][40] All but four of these were performed in North America, usually in a tertiary care setting, and all involved intense behavioural management support. Follow-up periods for the majority of studies were 6 months or less.…”
Section: The Opportunities In Adolescent Researchmentioning
confidence: 99%
“…Seseorang yang secara fisik bugar dapat melakukan aktivitas fisik sehari-harinya dengan giat, memiliki risiko rendah dalam masalah kesehatan dan dapat menikmati olahraga serta berbagai aktivitas lainnya. 4,5 Widhalm dkk 6 tahun 2004 di Austria melakukan penelitian pada 14 anak obes yang diasramakan selama tiga minggu dengan program olahraga dan diet yang ketat. Didapatkan penurunan berat badan sebesar 4,7 kg, namun pada penelitian tersebut tidak dilaporkan pengaruhnya terhadap lemak tubuh.…”
unclassified